Correlations of Elderly Fitness Exercise with Fitness and Balance - Anna; Sri Wahyudati; Tri Nur Kristina (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives : To analyze the correlations of elderly fitness exercise with fitness measured by 6-minute walk test (6-MWT) and balance measured by Berg Balance Scale (BBS) of geriatrics in nursing home.Methods: Cross- sectional observational study of 51 elderly who lived in nursing home that conducted in December 2009 to January 2010.Attendance of subject doing elderly fitness exercise was rated by 2 months previously recorded to one month after trial. We recorded the weekly frequency of doing the exercise for 12 weeks (the 3 months). At the observation, fitness was measured by 6-MWT, balance was measured by BBS.Results: A positive and an significant correlation between number of exercise in 12 weeks of observation to 6-MWT was analyzed by Pearson correlation 0.418, p=0.002, and also positive and significant correlation to BBS was found 0.353, p=0.011. There were also positive and significant correlation between exercise frequency to 6-MWT which analyzed by Spearman’s correlation 0.408, p=0.003 andto BBS as well Spearman’s correlation 0.404, p=0.003.Conclusions:The Elderly fitness exercise improves geriatric fitness that measured by 6-MWT and also improves balance measured by BBS in nursing home. The frequent exercise perfomed also correlates to elderly fitness which measure by 6-MWT and to balance that measured by BBS.Keywords:Fitness,balance, eld erly, 6 minute walk test, berg balance scale, ecercise, geriatric fitness exercise